Antibiotic Treatment of Pulmonary Infections: An Umbrella Review and Evidence Map - Wu, Man; Yang, Xue; Tian, Jinhui; Fan, Hong; Zhang, Yonggang (Frontiers in Pharmacology, 2021)
Background: Considering the global burden of pulmonary infections, there is an urgent need for the optimal empirical antimicrobial therapy strategies for pulmonary infections, which should rely on the reliable evidence. Therefore, we aim to investigate the optimal treatment options for pulmonary infections in adults and assess the strength of that evidence. Methods: We searched PubMed, Embase, the Cochrane Library, and China Biology Medicine disc to identify systematic reviews and meta-analyses of randomized controlled trials (RCTs) focusing on antimicrobial treatments for pulmonary infections. The outcomes of the included meta-analysis should include all-cause mortality or clinical treatment success. For each meta-analysis, we estimated relative risk (RR) with 95% CI. We also created an evidence map to show the efficacy of each antimicrobial treatment strategy and the certainty of the evidence. Results: 26 meta-analyses and 2 new RCTs were included that contained 31 types compared of antimicrobial therapy strategies. We found that carbapenems was related to lower mortality than other β-lactams or fluoroquinolones alone or in combination with aminoglycosides for HAP patients (RR 0.76, 95%CI: 0.58-0.99). There was no statistical difference in all cause mortality between the other compared antimicrobial therapy strategies. As for clinical cure, treatment with fluoroquinolones was associated with better success versus macrolides or β-lactams alone for CAP patients in both the intention-to-treat (ITT) population (RR 1.22, 95%CI: 1.02-1.47) and clinically evaluable (CE) population (RR 1.37, 95%CI: 1.11-1.68). Treatment with carbapenems showed a better clinical cure over non-carbapenems for VAP patients (RR 1.21, 95%CI: 1.05-1.4). Adjunctive inhaled antibiotics comparing with intravenous antibiotics alone showed a benefit for VAP (RR 1.2, 95%CI: 1.05-1.35). In addition, adjunctive nebulized aminoglycoside for nosocomial pneumonia was associated with higher cure rate versus intravenous antibiotics alone in ITT population (RR 1.28, 95%CI: 1.04-1.57). While, no statistical difference in clinical cure was observed between other intervention groups. Conclusions: We cannot evaluate which antibiotic is the best choice for the treatment of pulmonary infection, however, carbapenems or adjunctive inhaled antibiotics showed a reasonable choice for HAP or VAP. While, we do not find statistical difference between most antimicrobial therapy strategies for CAP patients.